2010
DOI: 10.1111/j.1600-0501.2010.01965.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of two biochemical markers for the risk assessment of oral bisphosphonate-related osteonecrosis of the jaws: can they be utilized as risk markers?

Abstract: as a result of the s-CTX and s-OC testings at the diagnosis of BRONJ, the values of the two markers were decreased. The decrease of the s-OC values implies a problem during the bone-formation process. Therefore, we can assume that in this patient group, invasive dental surgery contributes to an increase in the risk of BRONJ incidence. This result may imply that, during bisphosphonate therapy, simultaneous consideration of s-CTX showing inhibition of bone resorption and s-OC indicating the degree of bone format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 27 publications
2
26
0
7
Order By: Relevance
“…The histopathological specimens obtained from patients that have been affected by BRONJ appears to be consistent among studies [37,[154][155][156][157][158][159][160].…”
Section: Histology Of Bronjsupporting
confidence: 82%
See 2 more Smart Citations
“…The histopathological specimens obtained from patients that have been affected by BRONJ appears to be consistent among studies [37,[154][155][156][157][158][159][160].…”
Section: Histology Of Bronjsupporting
confidence: 82%
“…Serum CTX is used in most oral bisphosphonate research and is a standard test for bone turnover [43,160].…”
Section: Bone Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…8 patients with BP-ONJ in the maxilla, 9 patients with BP-ONJ in the mandible, 2 patients with BP-ONJ in mandible and maxilla Jacobsen 2013 [18]RS CS14 patients with established BP-ONJ due to dental implantsOsteoporosis 5Breast cancer 5multiple myeloma 2prostate cancer 1lung cancer 1A I P ZAverage BP duration3.2 osteoporosis; 4.2 malignant disease14n.s.n.s.n.s.n.s.The authors state that implants placed posterior are of higher risk than implants in the anterior region.4 patients had implants in the posterior maxilla, 5 in the posterior mandible and 3 in the anterior mandible.In one patient implants were removed and new implants were inserted at the same site with continuing problems.In one patient a sinus lift was performed Famili 2011 [25]RS CS211 female patients with 592 dental implants, out of those 120 older than 50 y with 347 implants out of those 22 with BP and 75 implantsOsteoporosis 21 osteoarthritis 1A I<1 - > 5075n.s.At least 20n.s.All female patients with implant therapy from 01/2008 – 06/2010 were analyzed. Among those 22 with oral BP therapy.One implant did not heal and was successfully replaced Kwon 2011 [21]RS CCS but not focused on dental implants→ RS CSBiochemical bone markers were evaluated in 23 osteoporosis patients with established BP-ONJOsteoporosisA2.5 - 52n.s.n.s.n.s.n.s.It is not clear, when and how the 23 BP-ONJ patients were recruited. 61 BP control patients.2 patients developed BP-ONJ due to implantsCTX was evaluated at the time of ONJ diagnosis and not at the time point of any possible BP-ONJ triggering intervention. Koka 2010 [22]RS CS370 patients over 50 years old with 818 implants.…”
Section: Resultsmentioning
confidence: 99%
“…10,11,36 In a prospective study investigating the predictive value of BALP, CTX, and parathyroid hormone in BRONJ development, Lazarovici et al noted that among patients receiving intravenous BP therapy for cancer management, the mean BALP level did not differ significantly between BRONJ and non-BRONJ patients (22.32 versus 20.78 pg/mL, p=>0.05). 10 A large retrospective study from Memorial Sloan-Kettering Cancer Center found no trends in BALP and NTX values in bone metastasis patients before the diagnosis of ONJ.…”
Section: Discussionmentioning
confidence: 99%